Clive Forbes on his tricycle at the front steps of the Forbes house in Bonavista - Forbes Family (1924)
Various houses in Bonavista are seen in the background behind a white picket fence. Cataloguer's title. Clive Forbes (born 1921), oldest son of Dr. C.A. Forbes and Irene (Matthews) Forbes, married Evelyn Jepson. The Forbes Family Photograph Collection contains 449 family photos of Dr. Robert E. Forbes and his son, Dr. C.A. Forbes, both physicians who collectively served Bonavista and nearby communities for over 80 years from ca. 1874 to 1955. Most of the photos are in albums, although they have been digitized as separate items, and are predominantly from the 20th Century. Many of the photos from the 1940s-50s are of two of Dr. C.A. Forbes' daughters, Vivian (Forbes) Osterhaut and Kathleen (Forbes) Deir, as well as Kathleen's husband Jack Deir who served in the Royal Canadian Army Medical Corps during World War II. A small number of images appear to date from the late 19th Century and include coverage of the family of Irene Matthews, wife of Dr. C.A. Forbes.